The Water, Soap, Sanitation, and Handwashing Facilities are Associated with COVID-19 Transmission in 44 Countries - Amsal Amsal (Poltekita : Jurnal Ilmu Kesehatan, 2020)
Coronavirus 2019 (COVID-19) is currently a global pandemic. Public awareness about washing hands is important in preventing the spread of COVID-19. The purpose of this study was to determine the relationship between increased water sources, basic water services, improved sanitation facilities, basic hand washing facilities, soap and water availability with COVID-19 transmission in 44 countries. Using Demographic and Health Survey Data in 44 countries including data on populations living in households using improved water sources, basic water services, improved sanitation facilities, hand washing practices, basic hand washing facilities with soap and water availability, ownership of electricity, television, cellphones , and households consisting of only those aged> 65 years. Data is downloaded in the form of Excel. The COVID-19 case was reported by the Johns Hopkins University Center for Science and Systems Engineering (CSSE) on April 28, 2020 in 44 countries. DHS program data from 44 countries that are relevant to the CSSE Johns Hopkins University data are carried out linear regression tests and alternatives (spearman test) using SPSS 22. Relationships between variables by looking at the correlation coefficient and p value for each variable. The results of the study are presented in tabular form. Results: Increased water sources, basic water services, improved sanitation facilities, basic hand washing facilities, soap and water available in relation to COVID-19 transmission, with each correlation coefficient of 0.421, 0.506, 0.374, 0.243 and 0.399.